Genetic assessment of farmed Oreochromis mossambicus populations in South Africa - Mahlatse Fortunate Mashaphu; Gordon Craig O’Brien; Colleen Thelma Downs; Sandi Willows-Munro (PeerJ)
The global utilisation of Oreochromis spp. in freshwater aquaculture extends to South Africa. Here the native Mozambique tilapia (Oreochromis mossambicus) has been proposed as a priority species for regional aquaculture projects, although it is still not preferred over the non-native O. niloticus. There is limited understanding of the genetic diversity, and genetic differentiation of farmed O. mossambicus in South Africa. Using a suite of 14 microsatellite markers, the present study aimed to determine the origin and genetic diversity of four farmed O. mossambicus populations in KwaZulu-Natal and Mpumalanga provinces. Wild O. mossambicus from rivers surrounding the farms were included to trace the origin of farmed populations. Results revealed lower genetic diversity in farmed populations compared to wild populations. In particular, the University of Zululand population exhibited lower genetic diversity compared to the rest of the farmed populations. While most farmed populations closely resembled their local wild counterparts, the uMphafa ponds exhibited distinct genetic characteristics. Notably, some individuals from uMphafa shared genetic affinities with those from the Thukela River, suggesting that the Thukela River could be the source of this farmed population, or that farmed fish may have been introduced or escaped into the river. The study suggests that select farmed populations may have the potential for use in breeding and broodstock supplementation programs but emphasizes the importance of thorough genetic monitoring. However, before these populations can be considered for broodstock supplementation, further investigation is required to confirm their genetic integrity and rule out potential contamination from invasive species.